School meals and educational outcomes in rural Ethiopia - Poppe, Robert; Frölich, Markus; Haile, Getinet (Taylor & Francis, 2017)
We investigate the relationship between providing school meals programme and educational outcomes in Ethiopia. Using data from school catchment areas across rural Ethiopia, the paper examines the role played by programme modalities and their implementation. The results indicate that supplementing on-site school meals with take-home rations can be beneficial for concentration, reading, writing and arithmetic skills. The timing of the distribution of school meals is also found to play an important role.